Produkte und Dienstleistungen im Paket - Eine Analyse der strategischen Preissetzung - - N, N

Simultane bilatrale Verhandlungen - Die Zusammenstellung eines Sortiments - N, N

Netzwerkeffekte auf zweiseitigen Märkten - Eine ökonomische Betrachtung der Modelle - N, N

Optimale Projektverträge unter Kostenunsicherheit - N, N

How do differentiated goods affect coopetition? - N, N

Towards an Economic Theory of Destabilization War - Gries, Thomas; Haake, Claus-Jochen (Peace Economics, Peace Science and Public Policy)

Sustainability of coalitional equilibria within repeated tax competition - Brangewitz, Sonja; Brockhoff, Sarah (European Journal of Political Economy)

Stackelberg Competition among Intermediaries in a Differentiated Duopoly with Product Innovation - Manegold, Jochen
On an intermediate goods market we consider vertical and horizontal product differentiation and analyze the impact of simultaneous competition for resources and the demand of customers on the market outcome. Asymmetries between intermediaries may arise due to distinct product qualities as well as by reasons of different production technologies. The intermediaries compete on the output market by choosing production quantities sequentially and for the supplies of a monopolistic input supplier on the input market. It turns out that there exist differences in product quality and productivities such that an intermediary being the Stackelberg leader has no incentive to procure inputs, whereas in the role of the Stackelberg follower will participate in the market. Moreover, we find that given an intermediary is more competitive, his equilibrium output quantity is higher when being the leader than when being the follower. Interestingly, if the intermediary is less competitive and goods are complements, there may exist asymmetries such that an intermediary being in the position of the Stackelberg follower offers higher output quantities in equilibrium than when being in the position of the Stackelberg leader.
Keywords: Input Market; Product Quality; Quantity Competition; Stackelberg Competition; Product Innovation

Competition of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen (Theoretical Economics Letters)
On an intermediate goods market with asymmetric production technologies as well as vertical and horizontal product differentiation we analyze the influence of simultaneous competition for resources and customers. The intermediaries face either price or quantity competition on the output market and a monopolistic, strategically acting supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Moreover, the well-known welfare advantage of price competition can in general be no longer confirmed in our model with an endogenous input market and asymmetric intermediaries.

Competition in Markets with Intermediaries - Manegold, Jochen

Economic Aspects of Service Composition: Price Negotiations and Quality Investments - Brangewitz, Sonja; Hoof, Simon (Service-Oriented and Cloud Computing: 5th IFIP WG 2.14 European Conference, ESOCC 2016, Vienna, Austria, September 5-7, 2016, Proceedings)
We analyse the economic interaction on the market for composed services. Typically, as providers of composed services, intermediaries interact on the sales side with users and on the procurement side with providers of single services. Thus, in how far a user request can be met often crucially depends on the prices and qualities of the different single services used in the composition. We study an intermediary who purchases two complementary single services and combines them. The prices paid to the service providers are determined by simultaneous multilateral Nash bargaining between the intermediary and the respective service provider. By using a function with constant elasticity of substitution (CES) to determine the quality of the composed service, we allow for complementary as well as substitutable degrees of the providers' service qualities. We investigate quality investments of service providers and the corresponding evolution of the single service quality within a differential game framework.

An Economic Theory of 'Destabilization War' - Gries, Thomas; Haake, Claus-Jochen
While Islamic State is the most present example, it is a fact that in many places around the globe, throughout history initially small groups have tried to challenge and destabilize or even overthrow governments by means of terrorist and guerrilla strategies. Therefore, we answer two questions. Why does a small group of insurgents believe it can overthrow the government by turning violent, even if the government is clearly superior? And how does a conflict develop into terrorism, a guerilla war, or a major conventional civil war, or is resolved peacefully? We develop a formal model for rebels and government and derive optimal choices. Further, we focus on three elements as important ingredients of a "destabilization war". All three of these - large random events, time preference (which we relate to ideology), and choice of duration of fight - are rarely considered in formal conflict theory. We can answer the above two questions using game theory analysis. First, insurgents rise up because they hope to destabilize through permanent challenging attacks. In this context, large randomness is an important ally of rebels. While each individual attack may have a low impact, at some point a large random event could lead to success. Hence, the duration of activities is a constitutive element of this kind of armed conflict. Patience (low time preference), which may reflect rebels' degree of ideological motivation, is crucial. Second, the mode of warfare or the conflict resolutions that develop are generally path-dependent and conditioned on the full set of options (including compromise). Various conditions (level of funding, ease of recruitment, access to weapons) influence different modes of warfare or a peaceful compromise in a complex way.
Keywords: terrorism; civil war; conflict duration; game theory; stochastic process; ideology

Renegotiable vs. Non-Renegotiable Agreements - Theory and Applications - N, N

Wie wertvoll ist der Einzelne für das Team? - Performancemessung der Bundesligaspieler anhand der kooperativen Spieltheorie der Saison 2014/2015 - N, N

Automatisiertes Matching von Angebot und Nachfrage in der Kunststoffindustrie Ein Fallbeispiel in Kooperation mit der PINPOOLS GmbH - N, N

Der Einfluss von Netzwerken auf Gleichgewichtspreise - eine spieltheoretische Analyse - N, N

Hat vertikale Integration einen Einfluss auf die allgemeine Wohlfahrt? - N, N

Stabile Supply-Chains - Basierend auf der Theorie der Matching-Märkte - N, N

Die Berechnung von Machtindizes - ein Vergleich verschiedener Verfahren - N, N

Intermediaries in Buyer Seller Networks - N, N

Staatliche Regulierung in vertikal verbundenen Industrien - eine spieltheoretische Analyse - N, N

Pricing and Revenue Sharing of Bundles Using Game Theoretical Concepts - N, N

Strategic Formation of Customer Relationship Networks - Brangewitz, Sonja; Haake, Claus-Jochen; Möhlmeier, Philipp
We analyze the stability of networks when two intermediaries strategically form costly links to customers. We interpret these links as customer relationships that enable trade to sell a product. Equilibrium prices and equilibrium quantities on the output as well as on the input market are determined endogenously for a given network of customer relationships. We investigate in how far the substitutability of the intermediaries' products and the costs of link formation influence the intermediaries' equilibrium profits and thus have an impact on the incentives to strategically form relationships to customers. For networks with three customers we characterize locally stable networks, in particular existence is guaranteed for any degree of substitutability. Moreover for the special cases of perfect complements, independent products and perfect substitutes, local stability coincides with the stronger concept of Nash stability. Additionally, for networks with n customers we analyze stability regions for selected networks and determine their limits when n goes to infinity. It turns out that the shape of the stability regions for those networks does not significantly change compared to a setting with a small number of customers.

Competition and Product Innovation of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen
On an intermediate goods market we allow for vertical and horizontal product differentiation and analyze the influence of simultaneous competition for resources and customers on the market outcome. Asymmetries between intermediaries cannot arise just from distinct product qualities, but also from different production technologies. The intermediaries face either price or quantity competition on the output market and a monopolistic input supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Considering product innovation for symmetric productivities we derive equilibrium conditions on the investment costs and compare price and quantity competition. It turns out that on the one hand there exist product qualities and degrees of horizontal product differentiation for complements such that asymmetric investment equilibria fail to exist. On the other hand we find that there also exist product qualities and degrees of horizontal product differentiation for substitutes such that existence can be guaranteed if the investment costs are chosen accordingly.

Bilateral matching and bargaining games - Mikroökonomie, Lehrstuhl

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Praktikabilität des Adjusted Winner Verfahrens bei variablem Status Quo- Punkt und exogenen Einflüssen - Streck, Thomas

Simultane bilaterale Verhandlungen - Zur Zusammenstellung eines Sortiments - N, N

Cournot-Nash-Bertrand Wettbewerb im serviceorientierten Internet - N, N

Multilaterale Verhandlungen aus Produzentensicht - N, N

Produktdifferenzierung und Verhandlungsposition im duopolistischen Wettbewerb - N, N

Aggregating Online Reputation Feedback - N, N

Verhandlungserfolg durch Reduktion von Verhandlungsasymmetrien - eine Analyse mit dem Adjusted-Winner-Verfahren - N, N

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

Strategic and Cooperative Games in Network Economics - Röhl, Nils

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Constitutions and Social Networks - Mauleon, Ana; Röhl, Nils; Vannetelbosch, Vincent
The objective of this paper is to analyze the formation of group structures where individuals are allowed to engage in several groups at the same time. These structures are interpreted here as social networks. Each of the groups is supposed to have specific rules or constitutions governing which members may join or leave it. A social network is then considered to be stable if none of the groups is altered any more. Given this framework, we not only analyze which influence the constitutions have on network formation but we also provide requirements under which stable networks are induced for sure. Furthermore, by embedding many-to-many matchings into our setting, we apply our model to job markets with labor unions. To some extent the unions may provide job guarantees and, therefore, have influence on the stability of the job market.

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)
We consider the inner core as a solution concept for cooperative games with non-transferable utility (NTU) and its relationship to payoffs of competitive equilibria of markets that are induced by NTU games. An NTU game is an NTU market game if there exists a market such that the set of utility allocations a coalition can achieve in the market coincides with the set of utility allocations the coalition can achieve in the game. In this paper, we introduce a new construction of a market based on a closed subset of the inner core which satisfies a strict positive separability. We show that the constructed market represents the NTU game and, further, has the given closed set as the set of payoff vectors of competitive equilibria. It turns out that this market is not uniquely determined, and thus, we obtain a class of markets. Our results generalize those relating to competitive outcomes of NTU market games in the literature.

Incorporating Reputation Information into Decision-Making Processes in Markets of Composed Services - Jungmann, Alexander; Brangewitz, Sonja; Petrlic, Ronald; Platenius, Marie Christin (International Journal On Advances in Intelligent Systems (IntSys))
One goal of service-oriented computing is to realize future markets of composed services. In such markets, service providers offer services that can be ﬂexibly combined with each other. However, although crucial for decision-making, market participants are usually not able to individually estimate the quality of traded services in advance. To overcome this problem, we present a conceptual design for a reputation system that collects and processes user feedback on transactions, and provides this information as a signal for quality to participants in the market. Based on our proposed concept, we describe the incorporation of reputation information into distinct decision-making processes that are crucial in such service markets. In this context, we present a fuzzy service matching approach that takes reputation information into account. Furthermore, we introduce an adaptive service composition approach, and investigate the impact of exchanging immediate user feedback by reputation information. Last but not least, we describe the importance of reputation information for economic decisions of different market participants. The overall output of this paper is a comprehensive view on managing and exploiting reputation information in markets of composed services using the example of On-The-Fly Computing.

Decision Making under Asymmetric Information in Markets for Experience Goods: Empirical Evidence of Signaling Effects on Consumer Perceptions - Kaimann, Daniel

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)

Two-Stage Allocation Procedures - Röhl, Nils
Suppose some individuals are allowed to engage in different groups at the same time and they generate a certain welfare by cooperation. Finding appropriate ways for distributing this welfare is a non-trivial issue. The purpose of this work is to analyze two-stage allocation procedures where first each group receives a share of the welfare which is then, subsequently, distributed among the corresponding members. To study these procedures in a structured way, cooperative games and network games are combined in a general framework by using mathematical hypergraphs. Moreover, several convincing requirements on allocation procedures are discussed and formalized. Thereby it will be shown, for example, that the Position Value and iteratively applying the Myerson Value can be characterized by similar axiomatizations.

Cooperative Transfer Price Negotiations under Incomplete Information - Brangewitz, Sonja; Haake, Claus-Jochen
In this paper, we analyze a model in which two divisions negotiate over an intrafirm transfer price for an intermediate product. Formally, we consider bargaining problems under incomplete information, since the upstream division’s (seller's) costs and downstream division's (buyer's) revenues are supposed to be private information. Assuming two possible types for buyer and seller each, we first establish that the bargaining problem is regular, regardless whether incentive and/or efficiency constraints are imposed. This allows us to apply the generalized Nash bargaining solution to determine transfer payments and transfer probabilities. Furthermore, we derive general properties of this solution for the transfer pricing problem and compare the model developed here with the existing literature for negotiated transfer pricing under incomplete information. In particular, we focus on the models presented in Wagenhofer (1994).
Keywords: Transfer Pricing; Negotiation; Generalized Nash Bargaining Solution; Incomplete Information

Dynamic One-to-One Matching: Theory and a Job Market Application - Stroh-Maraun, Nadja

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)
We establish a link between cooperative and competitive behavior. For every possible vector of weights of an asymmetric Nash bargaining solution there exists a market that has this asymmetric Nash bargaining solution as its unique competitive payoff vector.

Negotiating Transfer Prices - Haake, Claus-Jochen; Martini, Jan Thomas (Group Decision and Negotiation)

On the institutional design of burden sharing when financing external border enforcement in the EU - Haake, Claus-Jochen; Krieger, Tim; Minter, Steffen (International Economics and Economic Policy)

Stability of Coalitional Equilibria within Repeated Tax Competition - Brangewitz, Sonja; Brockhoff, Sarah
This paper analyzes the stability of capital tax harmonization agreements in a stylized model where countries have formed coalitions which set a common tax rate in order to avoid the inefficient fully non-cooperative Nash equilibrium. In particular, for a given coalition structure we study to what extend the stability of tax agreements is affected by the coalitions that have formed. In our set-up, countries are symmetric, but coalitions can be of arbitrary size. We analyze stability by means of a repeated game setting employing simple trigger strategies and we allow a sub-coalition to deviate from the coalitional equilibrium. For a given form of punishment we are able to rank the stability of different coalition structures as long as the size of the largest coalition does not change. Our main results are: (1) singleton regions have the largest incentives to deviate, (2) the stability of cooperation depends on the degree of cooperative behavior ex-ante.

Learning by Trading in Infinite Horizon Strategic Market Games with Default - Brangewitz, Sonja
We study the consequences of dropping the perfect competition assumption in a standard infinite horizon model with infinitely-lived traders and real collateralized assets, together with one additional ingredient: information among players is asymmetric and monitoring is incomplete. The key insight is that trading assets is not only a way to hedge oneself against uncertainty and to smooth consumption across time: It also enables learning information. Conversely, defaulting now becomes strategic: Certain players may manipulate prices so as to provoke a default in order to prevent their opponents from learning. We focus on learning equilibria, at the end of which no player has incorrect beliefs — not because those players with heterogeneous beliefs were eliminated from the market (although default is possible at equilibrium) but because they have taken time to update their prior belief. We prove a partial Folk theorem à la Wiseman (2011) of the following form: For any function that maps each state of the world to a sequence of feasible and strongly individually rational allocations, and for any degree of precision, there is a perfect Bayesian equilibrium in which patient players learn the realized state with this degree of precision and achieve a payoff close to the one specified for each state.

Coalitional and Strategic Market Games - Brangewitz, Sonja

Proportionality and the power of unequal parties - Dimitrov, Dinko; Haake, Claus-Jochen (International Journal of Economic Theory)
In this paper we introduce the concept of an overall power function that is meant to combine two sources of a party’s power in a parliament. The first source is based on the possibilities for the party to be part of a majority coalition and it is typically modeled using a cooperative simple game. The second source takes into account parties’ asymmetries outside the cooperative game and it is displayed by a vector of exogenously given weights. We adopt a normative point of view and provide an axiomatic characterization of a specific overall power function, in which the weights enter in a proportional fashion.

Prozedurale Ansätze zur Lösung mehrdimensionaler Verhandlungsprobleme - Stroh-Maraun, Nadja

Stability and Nash implementation in matching markets with couples - Haake, Claus-Jochen; Klaus, Bettina (Theory and Decision)

Monotonicity and Nash implementation in matching markets with contracts - Haake, Claus-Jochen; Klaus, Bettina (Economic Theory)

DIVIDING BY DEMANDING: OBJECT DIVISION THROUGH MARKET PROCEDURES - Haake, Claus-Jochen (International Game Theory Review)
We discuss a model, in which two agents may distribute finitely many objects among themselves. The conflict is resolved by means of a market procedure. Depending on the specifications, this procedure serves to achieve bargaining solutions such as the discrete Raiffa solution, the Kalai-Smorodinsky solution and the Perles-Maschler solution. The latter is axiomatized using the superadditivity axiom, which in the present context is readily interpreted as resolving a specific source of conflict potential.

Stable governments and the semistrict core - Dimitrov, Dinko; Haake, Claus-Jochen (Games and Economic Behavior)

The Shapley value of phylogenetic trees - Haake, Claus-Jochen; Kashiwada, Akemi; Su, Francis Edward (Journal of Mathematical Biology)

Two support results for the Kalai–Smorodinsky solution in small object division markets - Haake, Claus-Jochen (Mathematical Social Sciences)

On Maskin monotonicity of solution based social choice rules - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)

Comments on: Transversality of the Shapley value - Haake, Claus-Jochen (TOP)

A note on the paradox of smaller coalitions - Dimitrov, Dinko; Haake, Claus-Jochen (Social Choice and Welfare)

Bundling in exchange markets with indivisible goods - Haake, Claus-Jochen; Klaus, Bettina; Dimitrov, Dinko (Economics Letters)

Government versus Opposition: Who Should be Who in the 16th German Bundestag? - Dimitrov, Dinko; Haake, Claus-Jochen (Journal of Economics)

Trading bargaining weights - Haake, Claus-Jochen; Ervig, Ulrike (Journal of Mathematical Economics)
We consider a model, in which two agents are engaged in two separate bargaining problems. We introduce a notion of bargaining weights (bargaining power), which is basically given by asymmetric versions of the Perles–Maschler bargaining solution. Thereby, we view bargaining power as ordinary goods that can be traded in an exchange economy.With equal initial endowment of bargaining power there exists aWalrasian equilibrium in this exchange economy such that the utility allocation in equilibrium coincides with the Perles–Maschler bargaining solution of the aggregate bargaining problem. Equilibrium prices are given by the primitives of the two bargaining problems.

Bidding for envy-freeness: A procedural approach to n-player fair-division problems - Haake, Claus-Jochen; Raith, Matthias; Su, Francis Edward (Social Choice and Welfare)
We develop a procedure for implementing an efficient and envy-free allocation of m objects among n individuals with the possibility of monetary side-payments,assuming that players have quasi–linear utility functions. The procedure eliminates envy by compensating envious players. It is fully descriptive and says explicitly which compensations should be made,and in what order. Moreover,it is simple enough to be carried out without computer support. We formally characterize the properties of the procedure,show how it establishes envy-freeness with minimal resources,and demonstrate its application to a wide class of fair-division problems.